Applied high-intensity interval cardio yoga improves cardiometabolic fitness, energetic contributions, and metabolic flexibility in healthy adults - Park, So-Young; Yang, Woo-Hwi (Frontiers in Physiology, 2023)
Purpose: Currently, there is no interventional approach to increase the intensity of Surya Namaskar a popular hatha yoga sequence used worldwide. Therefore, this study investigated how tempo-based high-intensity interval cardio yoga (HIICY) and traditional-interval hatha yoga (TIHY) affects cardiometabolic fitness in active adults. Methods: Twenty physically active male and female individuals were randomly separated into HIICY (5 males, 5 females, 1.5s tempo) and TIHY (5 males, 5 females, 3s tempo) groups. The intervention included twelve exercise sessions for four weeks in both groups. Participants conducted a ramp test to determine their maximal oxygen uptake ( V ̇O2max), maximal velocity at V ̇O2max (vV ̇O2max), and maximal heart rate (HRmax). Afterward, they performed a 10-min high-intensity cardio yoga test (HICYT) to determine heart rate (HRpeak and HRmean), oxygen uptake (V ̇O2peak and V ̇O2mean), respiratory exchange ratio (RER), blood lactate concentrations (La − peak and ∆La − ), fat and carbohydrate oxidations (FATox, CHOox), and energetic contributions (oxidative; WOxi, glycolytic; WGly, and phosphagen; WPCr, total energy demand; Wtotal). Results: V ̇O2max and vV ̇O2max showed time and group x time interactions (p < 0.01, p < 0.0001, p < 0.001, respectively). V ̇O2max after HIICY was significantly higher than in pre-testing and following TIHY (p <0.001, p<0.0001, respectively). V ̇O2peak, V ̇O2mean, RER, HRpeak, and HRmean during the 10-min HICYT showed significant time effects (p < 0.05). ∆La − indicated a group x time interaction (p<0.05). Group x time effects for FATox at the 4th and 6th minute were observed (p < 0.05, respectively). Absolute (kJ) and relative (%) WOxi, WGly, and Wtotal showed time and group x time interactions (p < 0.05, p < 0.01, respectively). Furthermore, %WGly was reduced following HIICY (p < 0.05). Additionally, V ̇O2max and vV ̇O2max were highly correlated with WOxi in kJ (r = 0.91, 0.80, respectively). Moderate correlations were observed among CHOox, FATox, and absolute V ̇O2max. Conclusion: A 4-week period of HIICY improved cardiometabolic fitness, oxidative capacity, and metabolic flexibility compared with TIHY, in physically active adults. Therefore, HIICY is suitable as HY-specific HIIT and time-efficient approach for relatively healthy individuals.